(untitled) (Revista Paradigma, 2022)
The current research intended to study the existing contradictions between motherhood and prison, aiming at the effects of incarceration over the mother and prison-born child figures. Considering it’s a theoretical and qualitative investigation, it employed surveys and bibliographic selection of the most diverse studies about the theme, which constituted the essential theoretical framework to interpret the approached phenomena. Considering the analysis reach is, fundamentally, the same as the one employed by Criminology, the study demanded a multidisciplinary perspective, that is, it approached its object through many knowledge fields. In addition, a prescriptive exam was evidenced through the study due to its goal of reflecting about the solutions to the addressed ambivalence. Among other things, society’s operating logic through selective control systems that operate through a state policy of domain over the vulnerable was noted, it was attested how, beyond sex and gender, motherhood is influenced by other different social markers of differences, the many effects of child incarceration were testified, as well as the different phenomena involved in the matter, the effects of abrupt separation of mother and child were noted and, also, the precarious structure that they are submitted to. Finally, the study is concluded in the sense of utter incompatibility between the exercise of motherhood and prison due to the many paradoxes that make them irreconcilable.